The effect of various types of building roof materials on the cooling load - Ajeel Aljebur, Raheem Kadhim (2015)
Roof insulation is one of the most important strategies to reduce the electricity consumption in the building which lead to cost savings and reduce the emission of gases that pollute the environment directly. Therefore, Building information modelling took great interest in recent years in the world in terms of the design simulation of the buildings and choose the best design. This study aimed to evaluate the effect of various types of building roof materials on the cooling load. This study involved in selecting a particular building type (factory building) and the effect of the cooling load by using a various metal deck roofing with and without insulation. Case study in this project is a simple factory building consists of two floors, ground floor is a production space and the first floor is the factory's offices. The cooling load requirement for the building was calculated by using Auto desk Revit software. The results indicated that roof insulation is one of the most important strategies to reduce the cooling load and enhanced the electricity consumption in the building. 20% reduction in the space cooling lead to cost savings and reduce the emission of gases that pollute the environment directly.